The Effect of Motivation, Competence and Technological Facilities on the Performance of Civil Servants - Muh Said; Mustaking Mustaking (International Journal of Artificial Intelligence Research, 2022)
This research was conducted with the aim of: (1) To know and analyze the effect of motivation on the performance of Civil Servants at the Public Works and Spatial Planning Office of South Sulawesi Province; (2) to know and analyze the effect of competence on the performance of Civil Servants at the Public Works and Spatial Planning Office of South Sulawesi Province; (3) to know and analyze the effect of technological facilities on the performance of Civil Servants at the Public Works and Spatial Planning Office of South Sulawesi Province. This study uses primary data through a survey of 100 civil servants as a sample of all 336 civil servants. The survey was conducted in December 2021. Data were analyzed using Statistical Package for the Social Sciences (SPSS) software. The results of this study indicate that: (1) the motivation variable has a positive and significant effect on the performance of employees of the Public Works and Spatial Planning Office of South Sulawesi Province; (2) the competency variable has a positive and significant effect on improving the performance of employees of the Public Works and Spatial Planning Office of South Sulawesi Province; (3) the technology facility variable has a positive and significant effect on the performance of employees of the Public Works and Spatial Planning Office of South Sulawesi Province. This means that performance is influenced by motivation, competence and technological facilities. Good motivation at work as well as competence and technological facilities can encourage performance improvement. Research Recommendations: (1) Further research can be carried out for Public Works agencies at the Regency / City level. (2) Adding new independent variables such as age, length of service, level of education and others.